(untitled) (MATEMATIKA, 2004)
Kertas ini memaparkan persamaan-persamaan yang digunakan dalam permodelan sel litium. Persamaaan-persamaan yang terlibat dalam model ini termasuk persamaan pengangkutan jirim, hukum Ohm dan persamaan fluks bagi elektrod berongga didalam fasa elektrolid dan fasa pepejal. Persamaan-persamaan ini diselesaikan secara analitik, menggunakan kaedah penjelmaan Laplace, untuk mendapatkan profil kepekatan ion litium terhadap jarak dan masa. Katakunci: Penjelmaan Laplace; masalah serapan; sel litium This paper presents the equations used in the mathematical modeling of lithium cells. The model equations include the material balance equations, the Ohm’s Law and the flux equation for the porous electrodes in both the electrolyte and the solid phases. These equations are solved analytically, by means of Laplace transform, to give the concentration profile of the lithium ion concentration with respect to the distance and time. Keywords: Laplace transform; diffusion problem; lithium cell Closure matroid.